The Effects of Exercise Using Minnesota Strategy Problem Solving Model to Student Learning Outcomes and Critical Thinking Ability - NS Merisa; A Halim; Elmi Mahzum (Universitas Syiah Kuala, 2020)
This study aims to look at the effect of the Physics Problem Solving Exercise by using the